Dual infection with bluetongue virus serotypes and first time detection of serotype 5 in India - Hemadri, D.; Maan, Sushila; Rao, Prarthana Nagaraj; Putty, Kalyani; Krishnajyothi, Yadlapati; Reddy, G. Hanmanth; Kumar, Vinay; Batra, Kanisht; Reddy, Y. Vishnuvardhan; Maan, Narender Singh; Reddy, Yella Narasimha; Singh, Karam Pal; et al. (Wiley, 2017)
Bluetongue is endemic in India and has been reported from most Indian states. Of late, the clinical disease is most frequently seen in the states of Andhra Pradesh, Telangana (erstwhile Andhra Pradesh state), Tamil Nadu and Karnataka. Our analysis of diagnostic samples from bluetongue outbreaks during 2010–2011 from the state of Karnataka identified bluetongue virus (BTV) serotype 5 (BTV-5) for the first time in India. One of the diagnostic samples (CH1) and subsequent virus isolate (IND2010/02) contained both BTV-2 and BTV-5. Segment 2 (seg-2) sequence data (400 bp: nucleotides 2538–2921) for IND2010/02-BTV5, showed 94.3% nucleotide identity to BTV-5 from South Africa (Accession no. AJ585126), confirming the virus serotype and also indicating that Seg-2 was derived from a Western topotype, which is in contrast to serotype 2, that belongs to an Eastern topotype. BTV-5 has been recently reported from Africa, China, French islands and the Americas. Although the exact source of the Indian BTV-5 isolate is still to be confirmed, recent identification of additional exotic serotypes in India is of real concern and might add to the severity of the disease seen in these outbreaks.